2004
DOI: 10.1016/j.virol.2004.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the hepatitis C virus RNA replication complex associated with lipid rafts

Abstract: The mechanism and machinery of hepatitis C virus (HCV) RNA replication are still poorly characterized. Our previous study has shown that HCV RNA synthesis occurs on a lipid raft membrane structure [J. Virol. 77 (2003) 77 4160]. In this study, we further characterized these replication complexes (RCs) in Huh-7 cells that support active RNA replication of a subgenomic HCV replicon. Biochemical analysis showed that these membrane structures were resistant to Nonidet P-40 or Triton X-100 (TX-100) at 4 degrees C wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
234
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 247 publications
(254 citation statements)
references
References 80 publications
17
234
1
Order By: Relevance
“…This complex involves an isoprenoid protein called geranylgeranyl pyrophosphate, which is attached to specific G proteins via a process called protein prenylation. 31 In vitro studies of various statins have shown depletion of specific nonsterol isoprenoids (particularly geranylgeranyl pyrophosphate) that are generated via mevalonate metabolism. The availability of fewer lipid rafts for replication seems to be a plausible explanation for at least some of the anti-HCV properties of statins.…”
Section: Discussionmentioning
confidence: 99%
“…This complex involves an isoprenoid protein called geranylgeranyl pyrophosphate, which is attached to specific G proteins via a process called protein prenylation. 31 In vitro studies of various statins have shown depletion of specific nonsterol isoprenoids (particularly geranylgeranyl pyrophosphate) that are generated via mevalonate metabolism. The availability of fewer lipid rafts for replication seems to be a plausible explanation for at least some of the anti-HCV properties of statins.…”
Section: Discussionmentioning
confidence: 99%
“…PTB was associated with a DRM structure containing HCV NS proteins and RNA Previous studies have shown that HCV RCs were resistant to detergent treatment [8,29,31].…”
Section: Ptb Localized In Membrane Fractions Of Replicon Cellsmentioning
confidence: 98%
“…The membrane flotation assay was performed as previously described [31]. Briefly, Cells were first lysed in 1 ml of hypotonic buffer (10 mM Tris-HCV [pH 7.5], 10 mM KCl, 5 mM MgCl 2 ) and passed through a 25-gauge needle 20 times.…”
Section: Membrane Flotation Detergent Solubilization and Immunoblotmentioning
confidence: 99%
See 2 more Smart Citations